Landscape-scale factors determine occupancy of the critically endangered central rock-rat in arid Australia: The utility of camera trapping. (November 2015) - McDonald, Peter J.; Griffiths, Anthony D.; Nano, Catherine E.M.; Dickman, Chris R.; Ward, Simon J.; Luck, Gary W.
Abstract: The challenges of sampling rare fauna limit efforts to understand and mitigate the factors that restrict their distribution. Camera traps have become a standard technique for sampling large mammals, but their utility for sampling small, rare species remains largely unknown. The central rock-rat ( Zyzomys pedunculatus ) is critically endangered and restricted to rugged range country in central Australia. Using Z. pedunculatus as a focal species, we sought to evaluate the effectiveness of camera trapping for sampling small mammals in this environment and to better understand the factors driving the occurrence of this species. We installed baited camera traps at 50 sites across 1795 ha of core refuge habitat for Z. pedunculatus . We recorded all six species of small mammals known previously from this area, including the highly detectable Z. pedunculatus at five sites. Occupancy modelling showed that distance to the nearest occupied site was the most important predictor of Z. pedunculatus occurrence, suggesting that this rodent occurs in discrete sub-populations within the matrix of refuge habitat. Fire history and ruggedness may also influence occupancy of Z. pedunculatus at the landscape-scale and could assist in locating additional sub-populations. At the site-scale, occupancy of Z. pedunculatus was high and there was no clear influence of any site-scale variables. Management of Z. pedunculatus will require protection and expansion of known sub-populations. We conclude that camera trapping provided useful and cost-effective insight into the factors limiting rock-rat distribution, and predict that it will become a standard tool for sampling rare small mammals in difficult-to-access environments. Highlights: Utility of camera traps for sampling small rare mammals remains largely unknown. We detected all 6 small mammal species from a mountain refuge using camera traps. Landscape-scale variables drove occupancy of critically endangered central rock-rat. Central rock-rat occurs in discrete sub-populations within matrix of refuge habitat. We predict camera traps will become a standard tool for sampling rare small mammals.